The Application of Tax Law to a Corporation's Bankruptcy Restricted in Indonesia - Rachmat Dwi Putranto; Anggoro Hendrawan; Marjan Miharja; Gunawan Nachrawi; Emil Salim (Budapest International Research and Critics University, 2021)
While the journey of a legal entity of the Company is limited in Indonesia in terms of carrying out its business in accordance with its purpose, there are occasionally unexpected events such as debts that impede the smooth operation of the company's cash, or even ongoing disputes with creditors that force the company to declare bankruptcy via court orders, even though bankruptcy is not mandatory. Everything comes to an end with the Company. The Limited Liability Company owes the state something, specifically tax. The Directorate General of Taxes of the Republic of Indonesia's Ministry of Finance is responsible for state taxes. If the Company's tax obligations are not met optimally, the company's management, in this case the Directors and Commissioners, is responsible for resolving them. The company owner entrusts the Board of Directors with the responsibility of carrying out the responsibilities imposed by its authority in a limited company and carrying out the task prudently in accordance with the prudential principle. The curator was involved in a party's bankruptcy to manage the assets of parties in bankruptcy and distribute them to creditors in compliance with applicable rules and regulations.